Servant Leadership Behavior at Workplace and Knowledge Hoarding: A Moderation Mediation Examination - Zada, Shagufta; Khan, Jawad; Saeed, Imran; Jun, Zhang Yong; Vega-Muñoz, Alejandro; Contreras-Barraza, Nicolás (Frontiers in Psychology, 2022)
Servant leadership in a leadership philosophy emphasizes honesty, stewardship, and high moral standards while prioritizing the needs of subordinates. The moral concern of a servant leadership is to support others and put the needs of others first. We investigated the relationship between servant leadership, psychological safety and knowledge hoarding in accordance with social learning theory in a survey of 347 workers across 56 teams. The results of this study illustrate that servant leadership is negatively associated with knowledge hoarding and positively associated with psychological safety. We also found that a mastery climate moderated the relationship between servant leadership and knowledge hoarding. This study highlights the theoretical and practical implications that contribute to the body of knowledge. It helps organizations that the presence of servant leadership may discourage knowledge hoarding by providing a psychologically safe mastery climate.